The dynamics of industrial competition a North American perspective - Baldwin, John R. 1945- (Cambridge University Press, 1995)
The Dynamics of Industrial Competition, first published in 1995, describes the internal dynamics of industries using longitudinal data that make it possible to track firms over time. It provides a comprehensive picture of a number of different aspects of firm turnover in North America that arise from the competitive process - the entry and the exit of firms, the growth and decline of incumbent firms, and the merger process. Instantaneous and cumulative measures of market dynamics are provided by examining change in both the short and the long run. Using various measures of firm turnover to proxy the amount of competition, the study examines and contextualizes the relationship between industry performance and the intensity of the competitive process
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1970-1995; Statistik; Corporations / Canada / Statistics / Longitudinal studies; Industrial statistics / Canada / Longitudinal studies; Manufacturing industries / Canada / Statistics / Longitudinal studies; Competition / Canada / Statistics / Longitudinal studies; Dynamische Analyse; Industrie; Unternehmen; Wettbewerb; Kanada; USA; Nordamerika